O quanto o frete pode influenciar nas vendas do e-commerce - LIMA, Marcelo Vieira de; SANCTIS, Maria Eduarda de (183, 2023)
Atualmente, a gestão de transporte possui grande relevância para a maioria das empresas que buscam garantir a satisfação de seus clientes, fazendo com que seus produtos sejam destinados e entregues dentro do prazo estabelecido. Esta relevância aumenta quando pensada sob a ótica do e-commerce que visa facilitar a vida do consumidor, fazendo com que suas compras sejam mais rápidas e práticas. Porém, o problema se estabelece na seleção de um transporte adequado com um valor de frete que não acarrete problemas no custo do produto e nem no faturamento da empresa e analisar os impactos destes problemas no e-commerce é o que se propõe o presente trabalho. Refletindo sobre essa questão, o presente artigo também busca analisar a interferência que o frete provoca no comércio eletrônico. Para tanto utiliza-se de pesquisas bibliográficas e de um acompanhamento mês a mês dos impactos do frete em uma indústria de plástico reciclado, desde o momento da contratação do transporte para seus produtos até a finalização do processo vendas no e-commerce. Currently, transport management has great relevance for most companies that seek to ensure customer satisfaction, ensuring that their products are destined and delivered within the established deadline. This relevance increases when thought from the perspective of e-commerce that aims to make life easier for consumers, making their purchases faster and more practical. However, the problem is established in the selection of an adequate transport with a freight value that does not cause problems in the cost of the product or in the company's billing and analyzing the impacts of these problems in e-commerce is what the present work proposes. Reflecting on this issue, this article also seeks to analyze the interference that freight causes in e-commerce. For this purpose, bibliographical research and a month-to-month monitoring of the impacts of shipping on a recycled plastic industry are used, from the moment of contracting transport for its products until the completion of the e-commerce sales process.

Currently, transport management has great relevance for most companies that seek to ensure customer satisfaction, ensuring that their products are destined and delivered within the established deadline. This relevance increases when thought from the perspective of e-commerce that aims to make life easier for consumers, making their purchases faster and more practical. However, the problem is established in the selection of an adequate transport with a freight value that does not cause problems in the cost of the product or in the company's billing and analyzing the impacts of these problems in e-commerce is what the present work proposes. Reflecting on this issue, this article also seeks to analyze the interference that freight causes in e-commerce. For this purpose, bibliographical research and a month-to-month monitoring of the impacts of shipping on a recycled plastic industry are used, from the moment of contracting transport for its products until the completion of the e-commerce sales process.
How much shipping can influence e-commerce sales
Keywords: Transportes; Comércio eletrônico; Gestão e Negócios